Innovation in Motor Vehicle Tax Services at the Central Office of Local Revenue Management in the City of Cirebon - Saputra, Nicholas Bintang; Chaerunisa, Gusti Najwa; Permana, Ipik (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines innovations in Motor Vehicle Tax services at the Cirebon City P3DW Office, encompassing digital methods such as E-Samsat and Sambara, as well as conventional methods such as Mobile Samsat. The study employed qualitative descriptive methods through observation, interviews, and documentation. The results indicate that service innovations have been quite successful, but still face challenges such as limited access to technology and a lack of public understanding of digital services. Socialization efforts have been conducted through various media, but need to be further enhanced to improve tax service efficiency and public awareness.